Wokół rozważań nad międzynarodowym systemem ochrony dóbr kultury w konfliktach zbrojnych - Rutkowska, Patrycja (De Securitate et Defensione. O Bezpieczeństwie i Obronności, 2018)
The article outlines the international system for the protection of cultural property set up by UNESCO, under which cultural property located in a war zone is subject to protection and due care by the belligerent parties. Moreover, three levels of protection of cultural property in armed conflicts are presented, two of which – special protection and enhanced protection – are not widely used by the signatories of the 1954 Hague Convention, as evidenced by a limited number of cultural objects that have been chosen to be covered under those protection levels. One of the reasons for the low effectiveness of legislation pertaining to the protection of cultural property has been the inclusion of the concept of military necessity to the text of the Hague Convention, which is often invoked by warring factions as the justification for the violations of their duty of protecting cultural heritage.